Serum concentrations of polychlorinated dibenzo-p-dioxins among ceramicists. (January 2015) - Demond, Avery; Jiang, Xiaohui; Broadwater, Kendra; Meeker, John; Luksemburg, William; Maier, Martha; Garabrant, David; Franzblau, Alfred
Highlights: First measurements of serum dioxin levels in ceramicists. Some evidence of elevated dioxin levels relative to background. Measured levels not inconsistent with calculated levels reported in earlier study. Abstract: Polychlorinated dibenzo- p -dioxins (PCDDs) occur naturally in ball clay at elevated concentrations. Thus, persons who habitually work with clay may be at risk for exposure to PCDDs. An earlier case report provided some evidence of elevated PCDD levels in serum for long-term hobby ceramicists; however, no previous study has measured serum dioxin concentrations among ceramicists. This study measured PCDD serum levels for 27 individuals involved in ceramics making. The average residual, defined as the average of the [log measured serum lipid concentration – log background serum lipid concentration], was calculated and then tested to determine whether it was significantly different from zero. The p -values for the average residuals indicated that the serum lipid concentrations for several PCDD congeners were elevated relative to background. The number of significant residuals increased dramatically if the background concentrations were adjusted to account for the fact that they were not contemporaneous with the measurements for the ceramicists. The ratio of the 1, 2, 3, 6, 7, 8-HxCDD concentration to the 1, 2, 3, 7, 8, 9-HxCDD concentration was greater than 1.0, unlike in ball clay, suggesting that although long-term working with ball clay elevates the PCDD levels in serum somewhat, it is not the predominant source of the PCDD body burden for ceramicists.